Transmission electron diffraction study of a uniaxially-ordered high-mobility polymeric semiconductor. (4th January 2019) - Sasaki, Masayuki; Yamashita, Yu; Matsui, Hiroyuki; Oshima, Yoshifumi; Takeya, Jun
Abstract : By transmission electron diffraction, the local alignment of the PB16TTT polymeric semiconductor film, which was fabricated by compression with a glass blade, was estimated to consist of polymer chains arranged in a gentle winding state with 630 nm in radius of curvature. Abstract: Thin films of the polymeric semiconductor 2, 5-bis (3-hexadecylthiophen-2-yl) thieno (3, 2-b) thiophene obtained by compression with a glass blade exhibit high-carrier mobility. This enhanced performance has been attributed to the uniaxial alignment of the polymer molecules, although such alignment has not yet been demonstrated experimentally. In the present study, the local alignment of the polymer was estimated using transmission electron diffraction. The diffraction spots corresponding to π − π stacking layers (along the b -axis) showed an arc-like intensity distribution along with angles of 11.6°, 15.8° and 25.4° for selected areas having diameters of 70, 140 and 280 nm, respectively. This variation of the arc angle with diameter indicates that the polymer chains were arranged in a gentle winding state, with an average radius of curvature of ~630 nm. We conclude that, as expected, the high-carrier mobility of the polymer is related to its uniaxial alignment.